Molecular phylogeny of Burkholderia pseudomallei. - Pitt, T; Trakulsomboon, S; Dance, D (2000)
In terms of population structure, the species Burkholderia pseudomallei contains both clonal and non-clonal elements. By indexing variation in rRNA loci using the restriction endonuclease BamHI, we found that two ribotypes (types 1 and 3) are predominant in nature. Ribotype 3 is prevalent in Asian countries while ribotype 1 is more widespread. Some disease association was suggested for 4 ribotypes and strains of ribotype 4 were markedly associated with a fatal outcome. DNA macrorestriction (XbaI) profiles resolved by pulsed-field gel electrophoresis revealed great heterogeneity within the prevalent ribotypes and these profiles appeared to be reliable strain markers. Arabinose environmental strains were characterised by BamHI ribotypes that were markedly distinct form clinical and environmental isolates of the arabinose negative phenotype.